A Portable Electronic Transaction Device Based on Dual Interface Smart Card - Fuada, Syifaul; Alfaruq, Akhmad; Adiono, Trio (International Journal of Online and Biomedical Engineering (iJOE), 2020)
In recent years, electronic money facilities are increasingly diverse. It may replace conventional payments. The use of physical money can be diminished by utilizing digital money, which is realized by smartphone apps, bar codes, smart cards, and so on. The types of smart cards used also vary, and it can be divided into two methods, i.e., with contacts and without contact. In this work, we develop electronic transaction devices using dual interfaces: contact and contactless smart cards. As computational processing, we employ the Raspberry Pi 3 Model 3. It has a high processing speed, large memory, and small size. Hence our system enables to compact in a portable box. The features offered on our transaction device are as follows: transaction menu, balance check menu, payment menu, and top up menu. Also, we provide a device transaction connection to the printer. Therefore, proof of transactions can be printed out easily. The device developed also provides a touch panel display to display the transaction menu.